Investigating the Transcription and Translation's Issues for an Australian PhD Conducting Intervews in Bahasa Indonesia - Thoha, Nurianna (SBM ITB, 2009)
This paper discusses the issue of interviewing in a language other than English for a PhD study in an Australian University. The particular case of interviewing in Bahasa Indonesia language is discussed. The research paradigm is interpretive and the methodology is qualitative. This leads to the key issue of interpreting interviewees’ constructed meaning within one language and then through a process of translation providing an interpretation of meaning in a second language which remains ‘true’ to the original meaning offered by participants. The date were collected from seven large Indonesian Companies by using semi-structured interview which gave respondent the opportunity to tell their stories based on their own experiences because this study follows the tradition of ‘giving voice’ to respondents. Eight-eight interviews were conducted in Bahasa Indonesia and were recorded. All Eight-eight interviews were personally transcribed by the researcher. This ensured confidentially and allowed the researcher to get close to the data which facilitated sorting, coding and analysis. The transcription process involved an interpretive translation process from Bahasa Indonesia to English requiring extensive local knowledge not easly available to western researchers. The focus of this paper is on the difficulties that emerged during the transcription process since it involved a translation from Bahasa Indonesia to English. Because of different language structure between Bahasa Indonesia and English, a conscious research decision was made to create the second language translations as what I have termed ‘Bahasa English’. This hybrid language used English but with the nuances and language flow of Bahasa Indonesia. Other challenges were encountered during the analysis stage, with include not all Bahasa Indonesia word’s can be translated to English, and there are some terms that are used differently in Bahasa Indonesia and in English. The need to develop a sound basis with English-only speaking supervisors led to the development of some analysis strategies which will be reported in this paper.Keywords: transcription, translation, English, Bahasa Indonesia